Atenolol, methyldopa, and chlorthalidone in moderate hypertension. Issue 6053 (8th January 1977) - Webster, J; Jeffers, T A; Galloway, D B; Petrie, J C; Barker, N P
Abstract : Combined treatment with low doses of different drugs is widely used for moderate hypertension. The effects of atenolol and methyldopa at two dose levels and in combination at the lower doses were studied in patients with moderate hypertension on continuous treatment with moderate hypertension on continuous treatment with chlorthalidone. The mean reduction in standing blood pressures obtained with atenolol 150 and 300 mg/day was about 27/17 mm Hg and with methyldopa 750 and 1500 mg/day about 28/14 mm Hg. Combined treatment with atenolol 150 mg/day and methyldopa 750 mg/day for four weeks resulted in a reduction of 38/25 mm Hg. No difference was observed between the two doses of methyldopa. The lower dose of atenolol was better than the lower dose of methyldopa in reducing lying and standing diastolic blood pressures. These findings show that in patients on continuous treatment with chlorthalidone the addition of atenolol alone or methyldopa alone or of atenolol and methyldopa in combination is effective in the treatment of moderate hypertension.